Macrorestriction analysis of streptococcus agalactiae (group B Streptococcus) isolated from Malaysia - Thong, Kwai Lin; Goh, Yee Ling; Leong, Wing Kong; Lim, Chin Theam; Ngeow, Yun Fong (Society for General Microbiology, 2004)
Streptococcus agalactiae or group B streptococci (GBS) often colonize the gastrointestinal and urogenital tracts of women, who may transmit these organisms to their offspring during the birth process. Using PFGE analysis, the genetic diversity of GBS was studied for strains isolated from pregnant women and their newborn infants in a teaching hospital. A total of 48 different PFGE profiles were obtained from 123 strains, with one profile (S1) appearing to be predominant among both groups studied, There was good overall correlation between the profiles obtained for strains from mother-infant pairs and for strains isolated from different body sites in the same individual. Occasional discrepancies seen in related body sites and among mother-infant pairs suggest concurrent carriage of different strains in the same individual as well as the possibility of an environmental source of organism for the neonate. The overall results demonstrated that many variants of GBS strains occur in Malaysia.